Proteomic Associations of N-terminal (NT)-pro hormone BNP (NT-proBNP) in Heart Failure with Preserved Ejection Fraction (HFpEF) - Azzo, Joe David (Circ Heart Fail, 2024)
BACKGROUND: N-terminal-pro natriuretic peptide (NT-proBNP) levels are variably elevated in heart failure with preserved ejection fraction (HFpEF), even in the presence of increased left ventricular filling pressures. NT-proBNP levels are prognostic in HFpEF, and have been used as an inclusion criterion for several recent randomized clinical trials. However, the underlying biologic differences between HFpEF participants with high and low NT-proBNP levels remain to be fully understood. METHODS: We measured 4,928 proteins using an aptamer-based proteomic assay (SOMAScan®) in available plasma samples from 2 cohorts: (1) Participants with HFpEF enrolled in the Penn Heart Failure Study (PHFS, n=253); (2) TOPCAT trial participants in the Americas (n=218). We assessed the relationship between SOMAScan®-derived plasma NT-proBNP and levels of other proteins available in the SOMAScan® assay version 4 using robust linear regression, with correction for multiple comparisons, followed by pathway analysis. RESULTS: NT-proBNP levels exhibited prominent proteome-wide associations in PHFS and TOPCAT cohorts. Proteins most strongly associated with NT-proBNP in both cohorts included sushi, von Willebrand factor type-A, EGF and pentraxin domain containing-1 (SVEP1; β(TOPCAT)=0.539; P<0.0001; β(PHFS)=0.516; P<0.0001), and angiopoietin-2 (ANGPT2; β(TOPCAT)=0.571; P<0.0001; β(PHFS)=0.459; P<0.0001). Canonical pathway analysis demonstrated consistent associations with multiple pathways related to fibrosis and inflammation. These included hepatic fibrosis and inhibition of matrix metalloproteases. Analyses using cut-points corresponding to estimated quantitative concentrations of 360 pg/ml (and 480 pg/ml in atrial fibrillation) revealed similar proteomic associations. CONCLUSIONS: Circulating NT-proBNP levels exhibit prominent proteomic associations in HFpEF. Our findings suggest that higher NT-proBNP levels in HFpEF are a marker of fibrosis and inflammation. These findings will aid the interpretation of NT-proBNP levels in HFpEF and may guide the selection of participants in future HFpEF clinical trials.